The Strawsonian and Ledger Conception of Moral Responsibility - Steefan Cuypers (Ideas y Valores)
This paper returns to the very concept of moral responsibility. Its focus is not on the conditions but on the nature of moral responsibility. First, it introduces the Strawsonian and ledger conceptions of moral responsibility. Next, it contrasts and compares these conceptions. Finally, it evaluates both conceptions and asks which is the right one. Though this article works toward further clarifying the concept of moral responsibility, its conclusion is open-ended.